P412 An exploratory analysis of associations between psycho-social factors and systemic inflammation among south african youth. (14th July 2019) - Henry, Ashley; Muema, Daniel; Akilimali, Ngomu; Laher, Fatima; Jaggernath, Manjeetha; Hornschuh, Stefanie; Smith, Patricia; Cotton, Laura; Bekinska, Mags; Smit, Jenni; Dietrich, Janan; Gray, Glenda; et al.
Abstract : Background: Psycho-social factors affect biological processes, including inflammation and immune response, yet their contribution to gender and socio-economic disparity of HIV is not well understood. In South Africa, 38% of new HIV infections occur in 15–24 year olds, with 3-times higher incidence among females. In this exploratory study, we examined associations between psycho-social factors and biomarkers of inflammation that may be linked to HIV acquisition in South African youth. Methods: Baseline plasma and linked cross-sectional survey data were obtained from the AYAZAZI study, which enrolled 425 HIV uninfected or HIV status-unknown youth (16–24 years old; 60% female) in Durban and Soweto (2014–2016). Survey data captured social and clinical determinants of health (e.g., gender, income, food insecurity, body mass index [BMI]) and psycho-social characteristics (depression, anxiety, stress, substance use). A random, gender-stratified subset of 39 HIV-negative participants was selected. Luminex ® assays were used to analyze 12 plasma biomarkers. Associations between biomarkers and social, clinical, and psycho-social factors were assessed using Spearman's rank correlation. Results: Median age was 18 (IQR: 17–20); 19/39 were female. Consistent with prior studies, high depression symptomology scores were associated with elevated pro-inflammatory (IFN-α2, IL-1α, IL-6, IL-12(p40), MIP-1ß) and anti-inflammatory (IL-4, IL-10) cytokines (all p<0.05). Low BMI correlated with elevated pro-inflammatory (IFN-α2, IFN-γ, IL-1α, IL-1ß, IL-6, IL-12(p70), IP-10 and TNF-α) and anti-inflammatory (IL-10) biomarker levels (all p<0.05). Associations were also observed between some biomarkers and indicators of anxiety, food insecurity, low income, and financial responsibility for dependents, which varied between sites. Conclusion: Results indicate that psycho-social, clinical, and socio-economic challenges are associated with inflammatory biomarker levels in South African youth. This suggests a link between social determinants of health and biological factors that modulate disease risk, possibly including inflammatory conditions associated with increased HIV transmission. Further analysis is required to confirm these results and investigate their implications for HIV prevention. Disclosure: No significant relationships.